Low Oxygen Stress During Early Development Influences Regulation of Hypoxia-Response Genes in Farmed Atlantic Salmon (Salmo salar). Issue 9 (1st September 2020) - Kelly, Tara; Johnsen, Hanne; Burgerhout, Erik; Tveiten, Helge; Thesslund, Tina; Andersen, Øivind; Robinson, Nicholas
Abstract: Survival and growth of developing salmonids are negatively affected by low oxygen levels within gravel nests in natural streams, and hypoxic stress is often experienced by farmed Atlantic salmon ( Salmo salar ) within hatcheries. Exposure to hypoxia during early development may have long-lasting effects by altering epigenetic marks and gene expression in oxygen regulatory pathways. Here, we examine the transcriptomic response to low dissolved oxygen (DO) in post-hatch salmon reared continuously in 30%, 60% or 100% DO from fertilization until start of feeding. RNA sequencing revealed multiple differentially expressed genes, including oxygen transporting hemoglobin embryonic α subunit ( hbae ) and EGLN3 family hypoxia-inducible factor 3 ( egln3 ) which regulates the stability of hypoxia inducible factor 1α (HIF-1α). Both hbae and egln3 displayed expression levels inversely correlated to oxygen concentration, and DNA methylation patterns within the egln3 promoter were negatively associated with the transcript levels. These results suggest that epigenetic processes are influenced by low oxygen levels during early development in Atlantic salmon to upregulate hypoxia-response genes.